Prolyl 4-hydroxylase subunit alpha-2 acts as a TRIM21 ubiquitination substrate to promote papillary thyroid cancer progression via the glycolytic pathway - Fengping Wu; Qian Liu; Jinkang Zhang; Dongkun Xu; Xue Jiang; Kun Zhang; YaZheng Chen; Xuliang Xia; Zhiqiang Jiang; Yuhong Shi; Wenling Tu (Cell Death and Disease)
Abstract Papillary thyroid cancer (PTC), the predominant thyroid cancer, exhibits different adverse outcomes. However, the underlying molecular mechanisms of PTC remain inadequately elucidated. An integrative analysis of multiple mRNA-seq datasets from Gene Expression Omnibus and The Cancer Genome Atlas reveals a crucial gene, prolyl 4-hydroxylase subunit alpha-2 (P4HA2), implicated in PTC progression. This study explored the expression pattern, functional role, and underlying molecular mechanism of P4HA2 in PTC. P4HA2 expression is significantly upregulated in PTC and correlates with aggressive clinicopathological features and a poor prognosis. P4HA2 knockdown effectively suppresses PTC cell proliferation, migration, and invasion, and induces apoptosis. Conversely, P4HA2 overexpression exerts opposing effects on these cancer cell phenotypes. In vivo assessments confirmed the tumor-promoting effects of P4HA2, including subcutaneous tumor formation and multiple-organ (lung and liver) metastasis. Multi-omics analyses identified glycolytic pathway activation as a hallmark of P4HA2-driven tumorigenesis, which was further validated by measuring the extracellular acidification rate and α-ketoglutarate level. Subsequent investigation revealed that tripartite motif-containing protein 21 (TRIM21) interacts with P4HA2 through the RING domain, promoting K48-linked and K63-linked ubiquitination followed by proteasome-dependent degradation of P4HA2. The knockdown of TRIM21 significantly enhances the proliferation, migration, and invasion of PTC cells, while also inducing apoptosis. Moreover, P4H inhibitors also displayed notable anti-tumor effects in PTC cells. These findings collectively elucidate a novel mechanism through which P4HA2 potentially contributes to PTC progression, providing a promising therapeutic target.